Review of the anti-noise method in the speech recognition technology - Liu, Jing; Xiang, Xinguang (2017 12th IEEE Conference on Industrial Electronics and Applications (ICIEA), 2017)
With the development of science and technology, the requirement in the aspect of dealing with the relationship between human and machine is higher and higher. Speech recognition is one subject based on the pattern recognition and is closely related to computer science, psychology, linguistics, and signal processing, etc. The key step of speech recognition is the pretreatment process of speech signal. This paper introduces three common anti-noise speech processing technology, i.e., speech enhancement algorithm, feature compensation technology, and model compensation technology. Finally, some existing problems are enumerated in the speech recognition technology.